DIAGNOSTIC VALIDITY OF CYTOLOGICAL IMPRINT IN THYROID FOLLICULAR NEOPLASM - Pustaka, I G. N.; Sudarsa, I W.; Golden, and N. (BALI MEDICAL JOURNAL, 2013)
Background: Preoperative fine needle aspiration biopsy/FNAB examination, imprint cytology and frozen section intraoperative has big implications for diagnosis and surgical strategy of thyroid nodules with follicular neoplasm cytology. FNAB and frozen section has its limitations, it is difficult to detect the presence of capsular and/or vascular invasion of thyroid follicular carcinoma. Whereas imprint cytology can preserve cellular overview (especially the cell nucleus), including the capsular and/or vascular invasion. In addition, imprint cytology is faster than frozen section. Frozen section examination could not indicate the presence of capsular and/or vascular invasion in most cases so that imprint cytology is used to replace frozen section as an alternative. Method: This research is a diagnostic test study using a descriptive design. This is a prospective study to assess the sensitivity, specificity, NPV, and PPV of imprint cytology in patients with thyroid follicular neoplasm cytology. Results: In our study; sensitivity, specificity, PPV, NPV, and accuracy of imprint cytology for follicular neoplasm was found as 84.21%, 95.45%, 94.12%, 87.50% and 90.24% respectively. The outcome was based on likelihood ratio value of 18.21 and the ROC curve, area under the curve obtained at 0.879 and Kappa value of 0.802. Conclusion: Imprint cytology has a value of a good diagnostic validity in the diagnosis of follicular neoplasm of thyroid nodules with sensitivity and specifity values of 84.21% and 95.45%. Imprint cytology is a technique that is simple, inexpensive, and has good reliability so that it can be used instead of frozen section.
Keywords: frozen, section, imprint, cytology, follicular, neoplasm